Astrocytic HIV-1 Nef Expression Decreases Glutamate Transporter Expression in the Nucleus Accumbens and Increases Cocaine-Seeking Behavior in Rats - Jessalyn Pla-Tenorio; Bethzaly Velazquez-Perez; Yainira Mendez-Borrero; Myrella L. Cruz; Marian T. Sepulveda-Orengo; Richard J. Noel (Pharmaceuticals)
Background/Objectives: Cocaine use disorder is an intersecting issue in populations with HIV-1, further exacerbating the clinical course of the disease and contributing to neurotoxicity and neuroinflammation. Cocaine and HIV neurotoxins play roles in neuronal damage during neuroHIV progression by disrupting glutamate homeostasis in the brain. Even with combined antiretroviral therapy (cART), HIV-1 Nef, an early viral protein expressed in approximately 1% of infected astrocytes, remains a key neurotoxin. This study investigates the relationship among Nef, glutamate homeostasis, and cocaine in the nucleus accumbens (NAc), a critical brain region associated with drug motivation and reward. Methods: Male and female Sprague Dawley rats were used to compare the effects of astrocytic Nef and cocaine by molecular analysis of glutamate transporters, GLT-1 and the cysteine glutamate exchanger (xCT), in the NAc. Behavioral assessments for cocaine self-administration were used to evaluate cocaine-seeking behavior. Results: The findings indicate that both cocaine and Nef independently decrease the expression of the glutamate transporter GLT-1 in the NAc. Additionally, rats with astrocytic Nef expression exhibited increased cocaine-seeking behavior but demonstrated sex-dependent molecular differences after the behavioral paradigm. Conclusions: The results suggest that the expression of Nef intensifies cocaine-induced alterations in glutamate homeostasis in the NAc, potentially underlying increased cocaine-seeking behavior. Understanding these interactions better may inform therapeutic strategies for managing cocaine use disorder in HIV-infected individuals.